العوامل المؤثرة في سرعة ونجاح تعلم اللغة الثانية - nurkholis nurkholis (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
There are several factors that can affect the success of an educator in teaching foreign languages, including the neighborhood where he lived, the learning environment, communication between students and teachers as well as the use of the mother tongue. Other factors that influence the success of learning a second language is contained in an educator, which includes age, preparation in teaching, learning capabilities and methods or media used in the learning process. And as good as the ability of a teacher without being followed by the methods and media are better then the learning process will not succeed. And so are, as well as any methods and media used, without any capacity of educators and mature age, then learning will not be successful. Besides these factors, the factors which come from inside a student also very influential, such as the level of intelligence and a willingness is there. Therefore if you want to study a foreign language or second language can be successful, then all the factors should support well. Key word: Factors, learning, foreign language.